Temporal and Hf isotope geochemical evolution of southern Finnish Lapland from 2.77 Ga to 1.76 Ga - Lauri, L. S.; Andersen, T.; Räsänen, J.; Juopperi, H. (2012)
The southern Finnish Lapland area in the central part of the Fennoscandian shield is a geologically complex zone comprising several Archean blocks and Paleoproterozoic supracrustal belts all of which are intruded by voluminous Paleoproterozoic granites (the central Lapland granitoid complex, CLGC). New in-situ single crystal zircon U-Pb age determinations coupled with Lu-Hf isotope data from the same zircons were acquired from five granitoid rocks and one amphibolitic rock sample from the southern Lapland area. The samples represent at least four distinct magmatic events (at ca. 2.77 Ga, 2.12 Ga, 1.81 Ga, and 1.76 Ga). The 2.77 Ga and the 1.81-1.76 Ga events have initial Hf isotope signatures implying that local Archean rocks represent the source for the younger granites. The 2.12 Ga event has a slightly more juvenile Hf isotope composition suggesting either that the source for the 2.12 Ga granites represents a different Archean block or that the source is composed of mixed Archean and Paleoproterozoic components. The Neoarchean source for the Paleoproterozoic granites may be traced through the CLGC all the way to the Jokkmokk area in Sweden and possibly to the Lofoten area in Norway.